The cultural values of the Sara Patanguna in strengthening harmonization among Ethnics in Baubau (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This article identifies the cultural values ​​of Sara Pataanguna in strengthening inter-ethnic harmony in Baubau, South-East Sulawesi Province. The research is qualitative research conducted in the area settled by various ethnic groups such as Buginese, Torajan, Balinese, Ambonese, Javanese, and Chinese. In collecting data, we used a documentation study, in-depth interviews, and observations. Data analysis in this study was conducted interactively through three activity lines, namely data reduction, presentation, and conclusion. The results show that the cultural values ​​of Sara Pataanguna were sufficient to contribute to social-ethical norms, which are the legacy of Buton's ancestors since the Buton Sultanate ruled the land. These cultural values ​​form the basis for the Butonese and the migrant's own values living in Baubau since, in principle, these values (from local Butonese and from the migrants) synergize each other. The presence of migrant ethnic groups contributes to cultural values ​​and mutual symbiosis of the social structure in Baubau.
Keywords: Cultural; Values; Ethnography; Ethnicity; Harmonization